Daubing, Materiality, and Prophecy in Ezekiel 13: 10–16 - Virnelson, Leslie (2024)
Ezekiel 13:10-16 has long been understood by translating the word [inline-graphic 01i] as "whitewash" or some kind of building material, on the assumption that v. 10 metaphorizes censured prophecy as building something in a shoddy and deceptive way. It is preferable to read [inline-graphic 02i] in this passage as [inline-graphic 03i] I, meaning something insipid, as a censorious reference to an underlying practice of inscribing prophecy. There are multiple examples of West Semitic inscriptions of divinatory messages, including most notably the Deir ‘Alla and Amman Citadel inscriptions. This suggestion aligns the usage of [inline-graphic 04i] clearly with related passages in Ezek 22:28 and Lam 2:14, and with the discussion of censured prophets ([inline-graphic 05i]) and their various activities throughout Ezekiel 13. Theories of space and materiality enrich the discussion of the purpose and meaning of inscriptions of prophecy and how they might have functioned in an ancient context underlying Ezekiel 13.
Keywords: Materiality; Prophecy; Space